Phthalates and phthalate metabolites in urine from Tianjin and implications for platelet mitochondrial DNA methylation - Li, Weixia; Guo, Liqiong; Fang, Junkai; Zhao, Lei; Song, Shanjun; Fang, Tao; Li, Chenguang; Wang, Lei; Li, Penghui (Frontiers in Public Health, 2023)
Background Phthalates (PAEs) are important synthetic substances in plastics, attracting much attention due to their potential effects on the cardiovascular system. Methods In this study, urine and blood samples from 39 individuals were collected in Tianjin, China. Phthalates and phthalate metabolites (mPAEs) were analyzed using gas chromatography-mass spectrometry (GC-MS) and high-performance liquid chromatography-mass spectrometry (HPLC-MS), respectively. The polymerase chain reaction (PCR) products from bisulfite-treated mitochondrial DNA (mtDNA) samples were analyzed using pyrosequencing technology. Results The detection frequencies for 9 PAEs varied from 2.56 to 92.31%, and those for 10 mPAEs varied from 30.77 to 100%. The estimated daily intakes (EDIs) and cumulative risk of PAEs were calculated based on the experimental statistics of urinary PAEs and mPAEs. For PAEs, the HIRfD (hazard index corresponding to reference doses) values of 10.26% of participants and the HITDI (hazard index corresponding to tolerable daily intake) values of 30.77% of participants were estimated to exceed 1, suggesting a relatively high exposure risk. The mtDNA methylation levels in the MT-ATP8 and MT-ND5 were observed to be lower than in the MT-ATP6. Mono-ethyl phthalate (MEP) and MT-ATP8 were positively correlated with triglyceride levels (p < 0.05). Based on the association of PAEs, mtDNA methylation, and triglycerides, the mediating role of mtDNA methylation between PAEs and cardiovascular diseases (CVDs) was analyzed in this study, but no mediated effect was observed. Conclusion The effects of PAE exposure on cardiovascular diseases (CVDs) should be investigated further.